2013
DOI: 10.1002/nau.22488
|View full text |Cite
|
Sign up to set email alerts
|

Does episiotomy protect against injury of the levator ani muscle in normal vaginal delivery?

Abstract: Episiotomy does not appear to be associated with injury to the levator ani muscle in its pubic insertion in normal vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Instrumental delivery is known to be a risk factor for injury to the levator ani, and is itself often associated with episiotomy . However, in an observational study of 194 women without instrumental delivery, we found that episiotomy was not an independent risk factor for avulsion of the levator ani . This supports the argument that episiotomy does not have major impact on the detachment of the pubovisceral‐puborectal part of the levator ani.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Instrumental delivery is known to be a risk factor for injury to the levator ani, and is itself often associated with episiotomy . However, in an observational study of 194 women without instrumental delivery, we found that episiotomy was not an independent risk factor for avulsion of the levator ani . This supports the argument that episiotomy does not have major impact on the detachment of the pubovisceral‐puborectal part of the levator ani.…”
Section: Discussionsupporting
confidence: 80%
“…This was an observational retrospective study of primiparous women with normal vaginal deliveries. It was performed by re‐analyzing data sets obtained in an earlier study of postpartum pelvic floor assessment by ultrasound in normal vaginal deliveries . Women included in the 2011 birth register of our hospital, a tertiary institution with 1911 deliveries in 2011, were recruited by telephone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new LAM avulsion after a second vaginal delivery was found in only one woman. The incidence (0.9%) of a new LAM avulsion after a second vaginal delivery was much lower than for a first vaginal delivery (13-36%) [1][2][3][4][5] .This suggests that women who have had a vaginal delivery without developing LAM avulsion should be advised that their risk of acquiring LAM avulsion in a subsequent vaginal delivery would be low. However, this low incidence might be attributed to the low rate (2/121 vaginal deliveries) of forceps delivery in our group.…”
Section: Discussionmentioning
confidence: 99%
“…Levator ani muscle (LAM) avulsion has been reported in 13-36% of women after vaginal delivery [1][2][3][4][5] . Most studies have focused on primiparous women and the obstetric risk factors resulting in this condition 2,3,6,7 .…”
Section: Introductionmentioning
confidence: 99%